Investigating the impact of value congruence on work engagement in EFL teachers: the role of teacher enthusiasm - Cao, Jing; Zhang, Weijing (Frontiers in Psychology, 2023)
This research aimed to investigate the influence of value congruence on EFL (English as a Foreign Language) teachers' work engagement, with a focus on the mediating role of teacher enthusiasm. A sample of EFL teachers (N = 453) in China participated in the study. Data were collected using self-report measures, including the Value Congruence Scale, Teacher Enthusiasm Scale, and Work Engagement Scale. Structural equation modeling was employed to analyze the data and test the proposed model. The results revealed that value congruence had a significant positive direct effect on work engagement. Furthermore, teacher enthusiasm was found to mediate the relationship between value congruence and work engagement. These findings suggest that when EFL teachers perceive a congruence between their personal values and the values upheld by their educational institutions, they are more likely to experience higher levels of work engagement, and this relationship is partially explained by their level of enthusiasm. The study contributes to the understanding of the factors that influence EFL teachers' work engagement and highlights the importance of value congruence and teacher enthusiasm in fostering a positive work environment. These findings have implications for the development of interventions and practices aimed at enhancing EFL teachers' well-being and job satisfaction.